Influences of Mothers’ Parenting Attitude, Parenting Efficacy, and Stress Levels on Children’s Social Skills (Medico Legal Update, 2021)
This study aimed to identify the influences of mohers’ parenting attitude, parenting efficacy, and stresslevels on children’s social skills. A total of 117 mothers rearing 4–7-year-old children were included in thisstudy. Data were collected using as elf-administered questionnaire from November 13 to 26, 2011. Collecteddata were analyzed using the IBM SPSS 20.0 program with descriptive statistics, t-test, one-way analysisof variance (scheffetestforpost-hoc), Pearson’s correlation, and multiple regressions. Mothers’ parentingattitude (permission) and efficacy were positively correlated, whereas mothers’ stress level was negativelycorrelated with children’s social skills. Children’s social skills were influenced by mothers’ parenting andmarital stress levels and children’s gender and birth order. In addition, mothers’ occupational so influenceschildren’s social skills. These results indicated that differences in gender and birth order should be consideredin providing interventions for mothers’ stress management.